Systemic Adverse Effects of Topical Clobetasol and Counterfeit Cosmetic Products on Iraqi Women - Teeba H. Sagban; Ausama Jaccob; Abdulla Yaqoub; Huda Khadim (المجلة العراقية للصيدلة, 2023)
Background: Topical corticosteroids (TCs) are widely used for dermatologic diseases. Unfortunately, there exists many adverse effects (local and systemic). These adverse effects are comparable to those observed when glucocorticoids are administered systemically, but they are typically less severe. Aim: To assess the systemic adverse effects of topical clobetasol (TCL) and counterfeit cosmetic products (CCP) on Iraqi women. Methods and patients: This was a cross-sectional observational study; carried out from October 2022 to March 2023. Patients visited the outpatient clinic of the Department Dermatology and Venereology in Abu-al Khasib Hospital in Basra City, Iraq. Patients may be categorized into two distinct groups: the first group of subjects utilized TCL (n=31), while the second group consisted of patients with CCP (n=32), and the remaining participants were designated as the control group (n=35). A specialized dermatologist conducted a clinical examination to make a diagnosis. A questionnaire was collected, and blood samples were obtained for laboratory investigations. Results: TCs suppressed vitamin D (Vit-D), interlukin-6 (IL-6), testosterone, and estrogen and reduced cortisol concentrations significantly. TCs elevated red blood cells (RBC), neutrophils percent (NEU%), and hemoglobin (HB) levels significantly and prolong bleeding time. While not affecting WBCs, PLT, MPV, MCH, MCV, ACTH, or insulin levels, with decreased in HCT, MCHC, Eos%, and Lym% for all groups in comparison to control group. Conclusion: Topical corticosteroids are extensively used, mostly for the treatment of dermatological conditions. However, they can be misused for their cosmetic effects as fairness creams. TCs misuse is a big problem in Iraq, resulting in massive skin effects and systemic deterioration, such as hematological and hormonal effects. Nevertheless, the general population remains ignorant of the systemic adverse effects. Educational activities targeting the public are suggested to address the systemic deterioration.